PEREDUKSIAN FRAUD AKUNTAN - Wicaksono, Satria Budi; Haryadi, Bambang; Lisa, Oyong (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to uncover the efforts of accountants to reduce fraud. The study uses an interpretive approach with a phenomenological method to see phenomena that are directly related to the symptoms that arise around humans that are organized in the sphere of interaction between the accountant profession, clients, and third parties. The data in this study were obtained from observations in the field by actively participating in each activity, in-depth interviews related to efforts to avoid fraudulent practices with people who are directly involved in the world of accountants. Data analysis was performed using noema and noesis analysis. The results showed that there were three efforts that accountants could make when they were employed, such as religiosity, professionalism, and materialism. After formulating the results based on an analysis of conversations with the informant, it can be concluded that what must be done by the accountant is to combine the three efforts and apply them to the work culture. Keywords: Fraud, Accountants, Phenomenology, Religiosity, Professionalism